Case Report: Decrypting an interchromosomal insertion associated with Marfan’s syndrome: how optical genome mapping emphasizes the morbid burden of copy-neutral variants - Bonaglia, Maria Clara; Salvo, Eliana; Sironi, Manuela; Bertuzzo, Sara; Errichiello, Edoardo; Mattina, Teresa; Zuffardi, Orsetta (Frontiers in Genetics, 2023)
Optical genome mapping (OGM), which allows to analyze ultra-high molecular weight (UHMW) DNA molecules, represents a response to the restriction created by short-read next-generationsequencing, even in those cases where the causative variant is a neutral copy-number-variant, thus insensitive to quantitative investigations. This study aimed to provide a molecular diagnosis to a boy with Marfan syndrome (MFS) and intellectual disability (ID) carrying a de novo translocation involving chromosomes 3, 4, and 13 and a 1.7 Mb deletion at the breakpoint of chromosome 3.No FBN1 alteration explaining his Marfan phenotype was highlighted.UHMW gDNA was isolated from the patient and his parents and processed via OGM. Genome assembly was followed by variant calling and annotation. Multiple strategies confirmed the results.The 3p deletion, which disrupted ROBO2, (MIM*602431) included three copy-neutral insertions.Two came from chromosome 13; the third contained 15q21.1 including the FBN1 from intron-45 onwards, thus explaining the MFS phenotype. We could not attribute the ID to a specific gene variant nor to the reshuffling of topologically associating domains (TADs). Our patient did not have vesicular reflux-2 as reported by missense alterations of ROBO2 (VUR2, MIM#610878), implying that reduced expression of all or some isoforms has a different effect than some of the point mutations. Indeed, ROBO2 expression pattern and its role as axon-guide suggests its partial deletion as responsible for the patient's neurological phenotype. Conclusion: OGM testing 1) highlights copy-neutral variants that could remain invisible if no loss of heterozygosity is observed and 2) is mandatory before other molecular studies in the presence of any chromosomal rearrangement for an accurate genotype-phenotype relationship.